A protocol for combining fluorescent proteins with histological stains for diverse cell wall components. (3rd January 2018) - Ursache, Robertas; Andersen, Tonni Grube; Marhavý, Peter; Geldner, Niko
Summary: Higher plant function is contingent upon the complex three‐dimensional (3D) architecture of plant tissues, yet severe light scattering renders deep, 3D tissue imaging very problematic. Although efforts to 'clear' tissues have been ongoing for over a century, many innovations have been made in recent years. Among them, a protocol called ClearSee efficiently clears tissues and diminishes chlorophyll autofluorescence while maintaining fluorescent proteins – thereby allowing analysis of gene expression and protein localisation in cleared samples. To further increase the usefulness of this protocol, we have developed a ClearSee‐based toolbox in which a number of classical histological stains for lignin, suberin and other cell wall components can be used in conjunction with fluorescent reporter lines. We found that a number of classical dyes are highly soluble in ClearSee solution, allowing the old staining protocols to be enormously simplified; these additionally have been unsuitable for co‐visualisation with fluorescent markers due to harsh fixation and clearing. Consecutive staining with several dyes allows 3D co‐visualisation of distinct cell wall modifications with fluorescent proteins – used as transcriptional reporters or protein localisation tools – deep within tissues. Moreover, the protocol is easily applied on hand sections of different organs. In combination with confocal microscopy, this improves image quality while decreasing the time and cost of embedding/sectioning. It thus provides a low‐cost, efficient method for studying thick plant tissues which are usually cumbersome to visualise. Our ClearSee‐adapted protocols significantly improve and speed up anatomical and developmental investigations in numerous plant species, and we hope they will contribute to new discoveries in many areas of plant research. Significance Statement: Different histological stains for lignin, cellulose and suberin can be combined with the ClearSee protocol, greatly extending our ability to co‐visualise cell walls with fluorescent markers.